1987
DOI: 10.1021/j100306a045
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the rate constant for the reaction mercapto + nitrogen dioxide

Abstract: at low pressure (~1 Torr) between 221 and 415 K and a negative temperature dependence was observed: kx = (2.9 ± 0.5) X 10"11 exp((240 ± 50)/7") cm3 molecule"1 s"1. The room temperature value for kx from this study is higher than three previous values. Secondary chemistry associated with high H2S concentrations in the earlier studies is believed to contribute to the discrepancies. DS was used to investigate the isotope effect for reaction 1 and no evidence has been observed for a primary.isotope effect, A:(DS +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 9 publications
(14 reference statements)
3
40
0
Order By: Relevance
“…27 HSO • , for instance, has been proposed to lie along the pathway from HS • to atmospheric H 2 SO 4 by way of reaction with ozone. [28][29][30][31][32] It has also been unambiguously demonstrated that CH 3 SO • is an intermediate in the gas phase photolysis of dimethyl sulfoxide. 33 In this paper we report a solution phase transient absorption study of aryl sulfoxide photolysis designed to characterize directly the proposed arylsulfinyl radical intermediate 1.…”
Section: Introductionmentioning
confidence: 97%
“…27 HSO • , for instance, has been proposed to lie along the pathway from HS • to atmospheric H 2 SO 4 by way of reaction with ozone. [28][29][30][31][32] It has also been unambiguously demonstrated that CH 3 SO • is an intermediate in the gas phase photolysis of dimethyl sulfoxide. 33 In this paper we report a solution phase transient absorption study of aryl sulfoxide photolysis designed to characterize directly the proposed arylsulfinyl radical intermediate 1.…”
Section: Introductionmentioning
confidence: 97%
“…This upper limit for k(298 K) is based on the study by Stachnik and Molina [1229] utilizing experiments sensitive to the production of OH. Somewhat higher upper limits of 1.0 × 10 -1-113 17 and 1.5 × 10 -17 were assigned by Friedl et al [472] and Wang et al [1421] respectively from the detection sensitivities for OH detection and SH decay respectively. An even higher upper limit by Black [148], based on the lack of SH decay, may have been complicated by SH regeneration.…”
Section: -104mentioning
confidence: 93%
“…In fact, HSO has been detected as a product by Leu and Smith [808], Bulatov et al [194], Schonle et al [1161], and Wang et al [1421]. The absence of a primary deuterium isotope effect, as observed by Wang et al [1421], coupled with the large magnitude of the rate constant suggests that the (four-center intermediate) channels producing SO + HNO and OH + SNO are of minor importance. No evidence for a three-body combination reaction was found by either Black [148] or Friedl et al [472].…”
Section: -104mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] The produced SH has widely attracted studies of its kinetic reactivity with some atmospheric species, [3][4][5][6][7][8][9][10] the related photodissociation dynamics and mechanism, [11][12][13][14][15][16][17] and astrochemical characterization in interstellar space. [18,19] Spectral characterization of SH(X 2 P) radicals yielded the molecular constants and interaction constants for L doublets and hyperfine splitting.…”
Section: Introductionmentioning
confidence: 99%